Targeting Non-Eosinophilic Immunological Pathways in COPD and AECOPD: Current Insights and Therapeutic Strategies - Razia DEM; Gao C; Wang C; An Y; Wang F; Liu L; Lin H (International Journal of COPD)
Dur E Maknoon Razia,1 Chencheng Gao,1 Chao Wang,1 Yiming An,1 Fang Wang,1– 3 Ling Liu,1 Hongqiang Lin1– 3 1College of Basic Medical Sciences, Jilin University, Changchun, 130021, People’s Republic of China; 2Jilin Provincial Science and Technology Innovation Centre for Secondary Development of Proprietary Chinese Medicines, Changchun, 130021, People’s Republic of China; 3Jilin Provincial Engineering Laboratory of Precision Prevention and Control for Common Diseases, Changchun, 130021, People’s Republic of ChinaCorrespondence: Ling Liu; Hongqiang Lin, College of Basic Medical Sciences, Jilin University, Xinmin Road 126, Changchun, 130021, People’s Republic of China, Tel +86 431 85619574, Email liuling1978@163.com; linhq@jlu.edu.cnAbstract: COPD is a multifactorial illness characterized by a long-term restriction of airflow and an inflammatory reaction in the lungs. The associated emphysema leads to the breakdown of alveolar proteins and abnormal expansion of the lung air spaces. Chronic bronchitis caused by the same disease can result in increased deposition of structural proteins, narrowing of the airways, and excessive mucus secretion leading to acute exacerbation of COPD (AECOPD). The most commonly prescribed medications for it, such as glucocorticoids and bronchodilators, provide important therapeutic benefits, but they also have negative side effects, including immunosuppression and infection. Therefore, it is necessary to develop medications for the treatment of COPD that specifically target the immune system and molecular components. This review focuses on non-eosinophilic aspects of immunological modulation in COPD management. Since, existing literature extensively covers eosinophilic inflammation, this review aims to fill the gap by examining alternative immunological pathways and their therapeutic implications. The findings suggest that targeting specific immune responses may enhance treatment efficacy while minimizing adverse effects associated with traditional therapies. In summary, this review emphasizes the importance of advancing research into non-eosinophilic immunological mechanisms in COPD, prescribing for the development of novel therapies that can more effectively manage this disease. Keywords: COPD, AECOPD, immunological targets, emerging therapeutic strategies